Transcriptional Changes Underlying Elemental Stoichiometry Shifts in a Marine Heterotrophic Bacterium - Chan, Leong-Keat; Newton, Ryan J.; Sharma, Shalabh; Smith, Christa B.; Rayapati, Pratibha; Limardo, Alexander J.; Meile, Christof; Moran, Mary Ann (Frontiers in Microbiology, 2012)
Marine bacteria drive the biogeochemical processing of oceanic dissolved organic carbon (DOC), a 750-Tg C reservoir that is a critical component of the global C cycle. Catabolism of DOC is thought to be regulated by the biomass composition of heterotrophic bacteria, as cells maintain a C:N:P ratio of ~50:10:1 during DOC processing. Yet a complicating factor in stoichiometry-based analyses is that bacteria can change the C:N:P ratio of their biomass in response to resource composition. We investigated the physiological mechanisms of resource-driven shifts in biomass stoichiometry in continuous cultures of the marine heterotrophic bacterium Ruegeria pomeroyi (a member of the Roseobacter clade) under four element limitation regimes (C, N, P, and S). Microarray analysis indicated that the bacterium scavenged for alternate sources of the scarce element when cells were C-, N-, or P-limited; reworked the ratios of biomolecules when C- and P- limited; and exerted tighter control over import/export and cytoplasmic pools when N-limited. Under S-limitation, a scenario not existing naturally for surface ocean microbes, stress responses dominated transcriptional changes. Resource-driven changes in C:N ratios of up to 2.5-fold and in C:P ratios of up to 6-fold were measured in R. pomeroyi biomass. These changes were best explained if the C and P content of the cells was flexible in the face of shifting resources but N content was not, achieved through the net balance of different transcriptional strategies. The cellular-level metabolic trade-offs that govern biomass stoichiometery in R. pomeroyi may have implications for global carbon cycling. Strong homeostatic responses to N limitation by heterotrophic marine bacteria would intensify competition with autotrophs. Modification of cellular inventories in C- and P-limited heterotrophs would vary the elemental ratio of particulate organic matter sequestered in the deep ocean.